Nucleotide sequence of the control regions for the glnA and glnL genes of Salmonella typhimurium. - Hanau, R (1983)
We have partially characterized a DNA fragment encoding glutamine synthetase in Salmonella typhimurium. Restriction mapping and RNA polymerase binding studies identified two regions within the fragment which exhibit promoter activity when fused to lacZ in pMC1403, a plasmid used to detect transcriptional and translational control signals. DNA sequence analysis revealed that one region encodes amino acids corresponding to the amino terminus of the glutamine synthetase protein. The second region codes for the amino acids corresponding to the carboxy terminus of glutamine synthetase followed by a 330-nucleotide sequence containing an ideal Pribnow heptamer and a possible translation initiation signal. The location of this region is analogous to the position of the beginning of the glnL gene identified in Escherichia coli, and it is likely that the Pribnow heptamer is the RNA polymerase binding site for the glnL gene.